Characteristics and 2‐year outcomes of dabigatran treatment in patients with heart failure and atrial fibrillation: GLORIA‐AF. (2nd July 2020) - Dubner, Sergio J.; Teutsch, Christine; Huisman, Menno V.; Diener, Hans‐Christoph; Halperin, Jonathan; Rothman, Kenneth J.; Ma, Chang‐Sheng; Chuquiure‐Valenzuela, Eduardo; Bergler‐Klein, Jutta; Zint, Kristina; Riou França, Lionel; Lu, Shihai; et al.
Abstract: Aims: This study aimed to describe baseline characteristics of patients with atrial fibrillation (AF) at risk of stroke with and without history of heart failure (HF) and report 2‐year outcomes in the dabigatran‐treated subset of a prospective, global, observational study (GLORIA‐AF). Methods and results: Newly diagnosed patients with AF and CHA2 DS2 ‐VASc score ≥ 1 were consecutively enrolled. Baseline characteristics were assessed by the presence or absence of HF diagnosis at enrolment. Incidence rates for outcomes in dabigatran‐treated patients were estimated with and without standardization by stroke (excluding HF component) and bleeding risk scores. A total of 15 308 eligible patients were enrolled, including 15 154 with known HF status; of these, 3679 (24.0%) had been diagnosed with HF, 11 475 (75.0%) had not. Among 4873 dabigatran‐treated patients, 1169 (24.0%) had HF, and 3658 (75.1%) did not; the risk of stroke was high (CHA2 DS2 ‐VASc score ≥ 2) for 94.3% of patients with HF and 85.8% without, while 6.0% and 7.0%, respectively, had a high bleeding risk (HAS‐BLED ≥ 3). Incidence rates of all‐cause death in dabigatran‐treated patients with and without HF, standardized for CHA2 DS2 ‐VASc and HAS‐BLED scores, were 4.76 vs. 1.80 per 100 patient years (py), with roughly comparable rates of stroke (0.82 vs. 0.60 per 100 py) and major bleeding (1.20 vs. 0.92 per 100 py). Conclusions: Patients with AF and history of HF may have greater disease burden at AF diagnosis and increased mortality rates vs. patients without HF. Stroke and major bleeding rates were roughly comparable between groups confirming the long‐term safety and effectiveness of dabigatran in patients with HF.